2016
DOI: 10.1371/journal.pone.0146339
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Seasonal and Interannual Patterns of Marine Mammal Strandings in Subtropical Western South Atlantic

Abstract: Understanding temporal patterns of marine mammal occurrence is useful for establishing conservation strategies. We used a 38 yr-long dataset spanning 1976 to 2013 to describe temporal patterns and trends in marine mammal strandings along a subtropical stretch of the east coast of South America. This region is influenced by a transitional zone between tropical and temperate waters and is considered an important fishing ground off Brazil. Generalized Additive Models were used to evaluate the temporal stranding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 61 publications
4
53
0
Order By: Relevance
“…Some gillnets killed penguins inside the no‐fishing area and some nets exceeded the allowed length of 16 km (Figure ). Furthermore, a study showed that the current mortality of the Franciscana dolphin remains similar to that before the implementation of this novel regulation (Prado et al, ). Our data suggest that current fisheries regulations in the region, including closures and gear restrictions, are ineffective at preventing Magellanic penguin mortality.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some gillnets killed penguins inside the no‐fishing area and some nets exceeded the allowed length of 16 km (Figure ). Furthermore, a study showed that the current mortality of the Franciscana dolphin remains similar to that before the implementation of this novel regulation (Prado et al, ). Our data suggest that current fisheries regulations in the region, including closures and gear restrictions, are ineffective at preventing Magellanic penguin mortality.…”
Section: Discussionmentioning
confidence: 98%
“…During the last decade, the number of penguin strandings along the Brazilian coast has increased (García‐Borboroglu et al, , ; Mäder, Sander, & Casa, ). Concomitantly, the increase in fishing effort (net size and number of boats) by the gillnet fishery in southern Brazil has increased the incidental mortality of various marine megafauna, especially the Franciscana dolphins ( Pontoporia blainvillei ) and green turtles ( Chelonia mydas ) (Monteiro et al, ; Prado, Mattos, Silva, & Secchi, ; Secchi, Kinas, & Muelbert, ). Similar to these megafauna species, penguins are long‐lived and low‐fecundity animals with delayed maturity (Boersma, ).…”
Section: Introductionmentioning
confidence: 99%
“…The current situation of overfishing for several artisanal fishing resources in the PLE, as demonstrated by this study, and for industrial resources in the coastal region as demonstrated by Haimovici and Cardoso (), requires the attention of fishery managers. However, there is a clear lack of proper management measures or enforcement in southern Brazil, as several threatened marine megafauna species are killed annually in high numbers and most of the fish resources are overexploited (Fogliarini, Bugoni, Haimovici, Secchi, & Cardoso, ; Haimovici & Cardoso, ; Prado, Mattos, Silva, & Secchi, , this study). From a governance context of lack of enforcement or ineffective management or conservation strategies, Dowling et al () suggested that the most effective measures would be spatial and temporal approaches, as for example, the establishment of no‐fishing zones or seasonal closures.…”
Section: Discussionmentioning
confidence: 80%
“…Prado et al [85] used 38 years of data on marine mammal stranding along the east coast of South America to analyze shifts in distributions and mortality rates in marine mammals. Five species made up 97% of all strandings: Franciscana dolphins (Pontoporia blainvillei), bottlenose dolphins (Tursiops truncatus), South American fur seals (Arctocephalus australis), subantarctic fur seals (Arctocephalus tropicalis), and South American sea lions (Otaria flavescens).…”
Section: Population and Evolutionary Ecologymentioning
confidence: 99%
“…= However, the authors note that overfishing of other species could lead to negative effects on fur seals. Marine mammals may be at risk due to fishing mortality [85], as well as indirect effects caused by fishing such as increased competition for food [86]. These long-term studies will be critical for the monitoring of such effects.…”
Section: Population and Evolutionary Ecologymentioning
confidence: 99%